2019
DOI: 10.48550/arxiv.1910.13797
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Matrix Poincaré inequalities and concentration

Abstract: We show that any probability measure satisfying a Matrix Poincaré inequality with respect to some reversible Markov generator satisfies an exponential matrix concentration inequality depending on the associated matrix carré du champ operator. This extends to the matrix setting a classical phenomenon in the scalar case. Moreover, the proof gives rise to new matrix trace inequalities which could be of independent interest. We then apply this general fact by establishing matrix Poincaré inequalities to derive mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…They showed that a matrix Poincaré inequality generically implies concentration bounds in the operator norm similar to those in the scalar case 1 . They then proceeded to prove matrix Poincaré inequalities for several interesting classes of measures (product [ABY19], Gaussian [ABY19], Strongly Rayleigh [ABY19, Kat19]) on a case by case basis, often mimicking the scalar proofs but requiring significant additional work to handle the noncommutativity of matrices.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They showed that a matrix Poincaré inequality generically implies concentration bounds in the operator norm similar to those in the scalar case 1 . They then proceeded to prove matrix Poincaré inequalities for several interesting classes of measures (product [ABY19], Gaussian [ABY19], Strongly Rayleigh [ABY19, Kat19]) on a case by case basis, often mimicking the scalar proofs but requiring significant additional work to handle the noncommutativity of matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Theorem 1.1 implies that any reversible Markov semigroup satisfying a Poincaré inequality satisfies an exponential matrix concentration inequality; in particular [ABY19, Theorem 1.1] holds with the "matrix Poincaré" assumption replaced by "Poincaré". It also allows us to deduce all of the matrix Poincaré inequalities derived in [ABY19,Kat19] from their known scalar counterparts, and yields new matrix Poincaré and concentration inequalities, notably for Completely Log Concave (i.e., Lorentzian [BH19]) measures via [ALGV19, Theorem 1.1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation